PENDAMPINGAN MENGGUNAKAN STRATEGI TUGAS MENGENAL MASALAH UNTUK MENINGKATKAN KEMAMPUAN MENYUSUN PROPOSAL PTK BAGI GURU BINAAN KOTA PALU - DORCE LIMBONG LEBOK (ACADEMIA: Jurnal Inovasi Riset Akademik, 2023)
Since the launch of one of the promotion requirements for the teaching profession, namely Scientific Writing, especially Classroom Action Research (PTK), it turns out that up to now there are still many teachers who do not understand conducting Classroom Action Research and compiling PTK results reports. Sensing this condition, the researchers provided assistance to trained teachers at Palu City Middle Schools. Mentoring uses the Problem Recognition Task strategy. The research subjects were Christian Religious Education teachers as trained teachers in the researcher's supervision area. The research design is collaborative School Action Research (PTS). The research was conducted in two cycles. Data collection techniques use written tests and observations. Data analysis was carried out descriptively, quantitatively and qualitatively. The results of the analysis for the implementation of the RPP in cycle I obtained a score of 102 (85%) qualitatively in the category "Quite appropriate", cycle II obtained a score of 113 (94.17%) qualitatively entering the category "Suitable". For initial understanding, all teachers prepared a PTK proposal of 54.17, qualitatively in the category "Good enough". In cycle I quantitatively a score of 69.17 was obtained, in the "Good" category, and in cycle II quantitatively a score of 85.00 was obtained, in the "Good" category. The teacher's initial ability to prepare PTK proposals was 33.02%, qualitatively in the "Not good" category. In cycle I, quantitatively there was an increase in the average percentage score of 63.89%, qualitatively "Good". Cycle II obtained an average percentage score of 80.40% and qualitatively "Good". ABSTRAKSejak diluncurkan salah satu persyaratan kenaikan pangkat bagi profesi guru yaitu Karya Tulis Ilmiah khususnya Penelitian Tindakan Kelas (PTK) ternyata sampai sekarang masih banyak guru yang belum memahami melakukan Penelitian Tindakan Kelas dan menyusun laporan hasil PTK. Merasakan kondisi tersebut peneliti melakukan pendampingan bagi guru binaan di SMP Kota Palu. Pendampingan menggunakan strategi Tugas Mengenal Masalah. Subyek penelitian adalah guru Pendidikan Agama Kristen sebagai guru binaan pada wilayah pengawasan peneliti. Rancangan penelitian adalah Penelitian Tindakan Sekolah (PTS) kolaboratif. Penelitian dilakukan dalam dua siklus. Teknik pengunpulan data menggunakan tes tulis dan pengamatan. Analisis data dilakukan secara diskriptif kuantitatif dan kualitatif. Hasil analisis untuk pelaksanaan RPP pada siklus I diperoleh skor sebesar 102 (85%) secara kualitatif masuk katagori â€Cukup sesuaiâ€, siklus II diperoleh skor 113 (94,17%) secara kualitatif masuk katagori â€Sesuaiâ€. Untuk pemahaman awal seluruh guru menyusun proposal PTK sebesar 54,17, secara kualitatif masuk katageri â€Cukup baikâ€. Pada siklus I secara kuantitatif diperoleh skor 69,17, masuk katageri â€Baikâ€, dan siklus II secara kuantitatif diperoleh skor 85,00, masuk katagori â€Baikâ€. Untuk kemampuan awal guru menyusun proposal PTK, sebesar 33,02 %, secara kualitatif pada katagori â€œKurang baikâ€. Pada siklus I, secara kuantitatif mengalami peningkatan rata-rata persentase skor sebesar 63,89 %, secara kualitatif â€œBaikâ€. Siklus II diperoleh rata-rata persentase skor sebesar 80,40 % dan secara kualitatif â€Baikâ€.